PMMA Sandwiched Bi2Te3 Layer as a Saturable Absorber in Mode-Locked Fiber Laser - Guobao Jiang; Yuan Zhou; Lulu Wang; Ying Chen (Advances in Condensed Matter Physics)
In this paper, we fabricated a PMMA sandwiched Bi2Te3 self-assembly layer as a saturable absorber device, which was used as a passive mode locker for ultrafast pulse generation at the telecommunication band. Nanosheets of Bi2Te3 as a bulk topological insulator were successfully synthesized through a solvothermal treatment and self-assemble method to form a thin film at a water-air interface. In order to transfer the Bi2Te3 self-assembly layer to the optical fiber end, we design a construction of two PMMA layers sandwiched self-assembly layer. By incorporating this saturable absorber into an erbium-doped fiber laser, femtosecond mode-locking operation was experimentally demonstrated. The output pulse width is about 505 fs. Our results indicate that PMMA sandwiched topological insulator layer structure could be an improvement technology in traditional PMMA transfer method and could be used as a long-term stable saturable absorber for the passively mode locking lasers.